Managing Seasonal Demand Surges: Sales Strategies for Homemade Cookie Businesses During the Ramadan Peak Season - Leony Angelina Rianita Putri; Ali Farhan (Research in Accounting Journal (RAJ), 2026)
This study analyzes the surge in demand for Leon Cookis homemade cookies during the peak Ramadan season, driven by the tradition of exchanging gift hampers, increased consumer purchasing power, and promotional activities through WhatsApp. The objective of this research is to identify the factors influencing the demand increase, examine the sales management strategies implemented by the business, and compare business performance during Ramadan and normal periods. A qualitative approach was employed through interviews with the business owner and direct observations of the production process. The findings reveal that the cookies are produced fresh based on customer orders, while affordable pricing is maintained through the direct procurement of ingredients from suppliers. As a result, monthly sales volume increased significantly from 15 to 150 jars during the Ramadan peak season. The business strategy focuses on a made-to-order production system and direct purchasing of raw materials to optimize efficiency and maintain product quality. A comparison between Ramadan and regular periods indicates substantially higher operational efficiency and sales performance during the Ramadan peak season.